Partial sialoadenectomy for the treatment of benign tumours in the submandibular gland. Issue 6 (June 2016) - Ge, N.; Peng, X.; Zhang, L.; Cai, Z.-G.; Guo, C.-B.; Yu, G.-Y.
Abstract: The conventional treatment for benign tumours arising in the submandibular gland (SMG) has always involved whole gland excision with the tumour. In light of developments in parotid gland functional surgery, this prospective study was performed to evaluate the effectiveness and safety of partial sialoadenectomy (PS) for benign tumours in comparison with conventional total sialoadenectomy (TS). Thirty-one consecutive patients with a preoperative diagnosis of benign tumour in the SMG were included in the study from December 2008 to December 2010. Eleven patients were treated with PS and 20 patients underwent conventional TS. Salivary gland function and surgery-related complications were assessed. No difference in resting saliva flow was found between the two groups before the operation, while this was significantly higher in the PS group than in the TS group at 1 year after surgery ( P  = 0.009). With regard to complications, there was less deformity in facial appearance in the PS group. There was no recurrence in any of the 31 patients during the follow-up period (range 41–82 months). It is believed that this modification to SMG surgery is consistent with the idea of functional and minimal invasive salivary gland surgery. This technique represents a good choice for the management of benign tumours of the SMG for appropriately selected cases.